Survey response rates: Trends and a validity assessment framework. (August 2022) - Holtom, Brooks; Baruch, Yehuda; Aguinis, Herman; A Ballinger, Gary
Survey methodology has been and continues to be a pervasively used data-collection method in social science research. To better understand the state of the science, we first analyze response-rate information reported in 1014 surveys described in 703 articles from 17 journals from 2010 to 2020. Results showed a steady increase in average response rate from 48% in 2005 to 53% in 2010 to 56% in 2015 and 68% in 2020; a marked increase in the number of surveys per published article from 1.27 in 2015 to 1.79 in 2020; and that variables that predict response-rate fluctuations over time are related to research design (e.g. data-collection medium), participant motivation (e.g. incentives), and researcher motivation (i.e. number of surveys per article). Second, we propose complementary information on contemporary response-rate norms and benchmarks with a response-rate validity assessment framework to gather evidence on accuracy of inferences based on a particular response-rate level. Implementing this validation process involves gathering information on the researcher–participant relationship, participant qualifications and motivation, survey length and complexity, and cultural and national context. Future survey research should implement the validity assessment framework in addition to reporting the response-rate value to better indicate a sample's quality, appropriateness, and representativeness.